Co-generation of hydrogen and electricity from biodiesel process effluents. (18th October 2019) - Kondaveeti, Sanath; Kim, In-Won; Otari, Sachin; Patel, Sanjay K.S.; Pagolu, Raviteja; Losetty, Venkatramana; Kalia, Vipin Chandra; Lee, Jung-Kul
Abstract: In this study, we apply a short-term voltage (0.2–0.8 V) to both crude glycerol (CG) and an anaerobic digestion (AD) effluent in a single-chamber microbial fuel cell (MFC) for power production. This improves the bioelectrogenesis in both CG (in MFC-1) and the AD effluent (in MFC-2), but higher power generation is attained in MFC-2. The use of domestic and synthetic wastewaters in the AD process leads to the generation of 195 and 350 mL H2 /L-medium, respectively. MFC-2 performs better than MFC-1 in terms of both voltage generation and chemical oxygen demand (COD) reduction. The application of 0.8 V yields a power density of 311 mW/m 2 (1.94 times higher than that of the control (160 mW/m 2 )). In addition, MFC-2 exhibits a 70% COD removal at 0.8 V, which decreases to 56% at 0.2 V. Thus, the application of a short-term voltage in MFC can stimulate both bioelectrogenesis and COD removal. Highlights: Application of external voltage to a microbial fuel cell (MFC) during acclimatization improves bioelectrogenesis. Dark fermentation with synthetic wastewater yields high H2 production. Higher power generation is noted with crude glycerol (CG) dark fermentation effluent over CG. Enhanced performance of MFC is proved at an applied voltage of 0.8 V after 24 h acclimatization.